Pengaruh Performance Appraisal, Reward Dan Punishment Terhadap Kinerja Karyawan the Alana Hotel & Convention Center Solo - Cindy Yovita Sari; Suparwi Suparwi; Emmelia Nadira Satiti (Sekolah Tinggi Pariwisata Sahid Surakarta, 2020)
HRD (Human Resources Department) is a department within a company that is responsible for handling Human Resources (HR) processing. The purpose of this study was to determine the implementation and effect of performance appraisal, reward, and punishment on the performance of employees of The Alana Hotel & Convention Center Solo. This type of research used by the author is a qualitative method. For the data collection technique, the writer used the interview method, documentation, observation, triangulation, and literature study. These results are from the recapitulation of the effect of performance appraisal, reward, and punishment on good employee performance, seen from the results of interviews with 8 employees, and based on the recapitulation of data results, that the effect of performance appraisal, reward, and punishment has an effect on employee performance.